Anthracene-based polyurethane networks: Tunable thermal degradation, photochemical cure and stress-relaxation. (August 2018) - Van Damme, Jonas; van den Berg, Otto; Vlaminck, Laetitia; Brancart, Joost; Van Assche, Guy; Du Prez, Filip
Graphical abstract: Highlights: Synthesis of anthracene-based polyurethane networks with different dimers having variable thermal stability. Establishing the structure-property relationship of the thermal scission behavior. Recuring the thermally dissociated films and coatings. Stress-relaxation in thin films by photo- and thermostimulated bond exchange. Abstract: Anthracene dimer diols having very different thermal stabilities have been incorporated in polyurethane networks. The thermal de-crosslinking of these networks was shown to be dependent on the anthracene dimer used, allowing tunable thermal degradation. This scission was studied using (HR-MAS) NMR, DSC and rheometry. The tunable thermal decrosslinking was validated as a technique to easily remove the coatings at their end-of-life. The UV irradiation of the thermally degraded materials allows for recuring the coatings to materials having similar properties. By simultaneous irradiation and heating of (partially) reversibly cross-linked networks, the networks were able to relief internal stress and adopt a new permanent shape.